2019
DOI: 10.1007/s00392-019-01447-5
|View full text |Cite
|
Sign up to set email alerts
|

Implant-based multi-parameter telemonitoring of patients with heart failure and a defibrillator with vs. without cardiac resynchronization therapy option: a subanalysis of the IN-TIME trial

Abstract: AimsIn the IN-TIME trial, automatic daily implant-based multiparameter telemonitoring significantly improved clinical outcomes in patients with chronic systolic heart failure and implantable cardioverter-defibrillator (ICD) or cardiac resynchronization therapy defibrillator (CRT-D). We compared IN-TIME results for ICD and CRT-D subgroups.MethodsPatients with LVEF ≤ 35%, NYHA class II/III, optimized drug treatment, no permanent atrial fibrillation, and a dual-chamber ICD (n = 274) or CRT-D (n = 390) were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…The REM-HF study confirmed these results, showing that RPM did not reduce the incidence of cardiovascular events in a heart-failure cohort [ 5 ]. In contrast, the IN-TIME and TIM-HF-2 trials were able to show a potential benefit on clinical outcomes by RPM surveillance [ 19 21 ]. Regarding economic aspects, RPM bears the potential to be a cost-efficient alternative to regular in-office device interrogations [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The REM-HF study confirmed these results, showing that RPM did not reduce the incidence of cardiovascular events in a heart-failure cohort [ 5 ]. In contrast, the IN-TIME and TIM-HF-2 trials were able to show a potential benefit on clinical outcomes by RPM surveillance [ 19 21 ]. Regarding economic aspects, RPM bears the potential to be a cost-efficient alternative to regular in-office device interrogations [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In practice, however, clinicians may have reservations about remotely assessing their most vulnerable and unwell patients. As described by Geller et al , 21 ‘in clinical practice telemedicine seems to be used mainly in patients with better prognosis, probably due to the belief that those who live longer may receive more (ie, prolonged) benefit from telemonitoring than sicker patients who should be seen in the office more frequently’ (p1124). Consequently, clinicians may require additional information on how RPM can be safely delivered in high-risk cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven RCTs have been conducted. [25][26][27][28][29][30][31][32][33][34][35] Of these, only three demonstrated a significant reduction in acute care use with a reduction in length of hospital stays 26 by 2.5 days (RPM=10.3±8.1 days, median: 8.0 days vs non-monitored group=17.5±19.9 days, median 10.5 days, p=0.027) and lower hospitalisation rates in the monitored group (37.1% vs 45.5%, p=0.045 31 ; hazard ratio (HR) 0.6, 0.42-0.79, p=0.002). 35 All remaining RCTs (n=6, 55%) showed no significant effect.…”
Section: Technologymentioning
confidence: 99%